Structural and behavioral reference model for IoT‐based elderly health‐care systems in smart home. (31st May 2019) - Ghasemi, Farideh; Rezaee, Ali; Rahmani, Amir Masoud
Summary: Increasing level of personal and social health and life expectancy has resulted in the growth of aged people population. Elderly care is an essential and costly issue in any society that should be addressed in researches. Elderly care has faced some problems such as elderly solitary, trained caregivers insufficiency, and increasing cost of late diagnosis of diseases and accident. Regarding to these problems, smart home technology can be used as an efficient solution. It provides an expertise, long‐term, and low‐cost care that empowers elderly to have an independent life. In this paper, we propose an architecture for a health‐care system in a smart home. In this architecture, rapid and timely diagnosis of environmental incidents and health risks causes reduction in costs of health care and relief. Given to the vital aspect of health‐care systems, the proposed architecture components and solutions are presented to meet quality attributes such as availability, performance, security, and interoperability. The proposed architecture evaluation is based on the Architecture Tradeoff Analysis Method (ATAM) scenario‐based approach. ATAM is a method for analysis and evaluation of software systems architecture. And quality attributes scenarios are examined to meet quality requirement. Compared with the previous works, more quality attributes are addressed in this paper. Abstract : In this paper, a monitoring system of elderly person's health care is presented in order to in time diagnosis of emergency cases. This system uses a set of sensors to monitor the elderly person's daily activities and health state. Quality attributes scenarios are examined to meet quality requirement. Compared with the previous works, more quality attributes including availability, performance, modifiability, interoperability, usability, and security are addressed in this paper.